Public Narratives and Ethnic Conflict Portrayal: Media Analysis of the Rohingya Conflict - Iqbal, Muhammad; Mukhlis; Fithra, Herman; Alwi, Said; Buto, Zulfikar Ali (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2024)
In Southeast Asia, ethnic conflicts are complex phenomena influenced by religious affiliations, nationalism, and citizenship rights. This study examines the role of media in shaping public narratives and perceptions of the Rohingya crisis, particularly in Aceh, Indonesia. Media analysis reveals that coverage provides practical insights into the consequences of refugee influx, highlighting social, humanitarian, and infrastructural impacts. Moreover, media diversifies understanding by presenting varied perspectives and linking ethnic conflicts with broader issues such as human trafficking. The study emphasizes how media narratives influence community attitudes towards Rohingya refugees in Aceh, reflecting shifts in acceptance or rejection based on portrayal. It underscores media's responsibility for accurate, balanced coverage crucial in shaping public understanding. Employing qualitative content analysis of print and online sources from 2023, this research examines media's depiction of the Rohingya conflict and refugee responses in Aceh. Findings contribute insights into media's role in public perception and its impact on refugee acceptance. This study advocates further media analysis to deeper understanding of complex ethnic conflicts, aiming to mitigate stereotypes and foster empathy towards refugees. Encourage balanced and diverse media reporting on ethnic conflicts to foster empathy and informed public dialogue, particularly in communities like Aceh. Support further research and education on the media's role in shaping perceptions to promote effective conflict resolution and humanitarian responses.